Improving the Surface Corrosion Resistance of AMX601 Magnesium Alloy by Acid–Alkaline Treatment - Anawati, Anawati; Asoh, Hidetaka; Ono, Sachiko (UI Scholars Hub, 2020)
A drawback of acid cleaning as surface finishing of magnesium (Mg) surface is the absence of a protective oxide film on its surface. Acid–alkaline treatment is proposed to enhance the surface corrosion resistance of AMX601 Mg alloy. Acid–alkaline treatment was conducted by first dipping the alloy in HNO3–H3PO4 solution and then immersing the al-loy in NaOH solution. The potentiodynamic polarization test in 0.9% NaCl solution at 37 °C revealed a nobler corro-sion potential of −1.36 VAg/AgCl and a lower corrosion current density of 36.0 µA•cm−2 of the acid–alkaline-treated spec-imen than the acid-treated (−1.44 VAg/AgCl, 89.7 µA•cm−2) and untreated (−1.52 VAg/AgCl, 40.0 µA•cm−2) specimens. Acid treatment induced a significantly higher surface roughness (20 µm) than acid–alkaline (10 µm) and grinding (0.5 µm) treatments because of the selective dissolution of the Mg matrix and the accumulation of intermetallic precipitates. The film formed on the acid–alkaline-treated specimen was thick and free of cracks, whereas that formed on the acid-treated specimen was thin and cleaved. The formation of a protective oxide film and the enrichment of cathodic intermetallic particles on the acid–alkaline-treated specimen enhanced the corrosion resistance of the surface.